Modified EPOCH for high‐risk non‐Hodgkin lymphoma in sub‐Saharan Africa. (9th November 2019) - Zuze, Takondwa; Ellis, Grace K.; Kasonkanji, Edwards; Kaimila, Bongani; Nyasosela, Richard; Nyirenda, Ruth; Tomoka, Tamiwe; Mulenga, Maurice; Chikasema, Maria; Tewete, Blessings; Mtangwanika, Asekanadziwa; Chiyoyola, Sarah; et al.
Abstract: Aggressive non‐Hodgkin lymphoma (NHL) is among the most common cancers in sub‐Saharan Africa (SSA), where CHOP is standard treatment and outcomes are poor. To address this, we treated 17 newly diagnosed adult patients in Malawi with Burkitt (n = 8), plasmablastic (n = 8), and primary effusion lymphoma (n = 1) with a modified EPOCH regimen between 2016 and 2019. Twelve patients (71%) were male and the median age was 40 years (range 16‐63). Eleven (65%) were HIV infected, median CD4 count was 218 cells/µL (range 9‐460), and nine (82%) had suppressed HIV RNA < 400 copies/mL. Patients received a median of six cycles (range 2‐8) and median follow‐up was 14 months (range 2‐34) among patients still alive. Grade 3/4 neutropenia was observed in 26% of cycles and in 65% of patients. Sixteen (94%) responded to EPOCH and 10 (59%) achieved a complete response. One‐year overall survival (OS) was 62% (95% confidence interval [CI], 42%‐91%). Five patients (29%) died from progressive NHL and three (18%) from treatment‐related complications. These data suggest EPOCH with setting‐appropriate modifications may be a practical, safe, and effective option for improving high‐risk NHL outcomes in Malawi and comparable settings, which deserves further prospective evaluation. Abstract : We evaluated the safety and efficacy of EPOCH, with modifications as required for local administration, for patients with high‐risk NHL in Malawi. We treated 17 newly diagnosed adult patients in Malawi with Burkitt (n = 8), plasmablastic (n = 8), and primary effusion lymphoma (n = 1) with a modified EPOCH regimen between 2016 and 2019. Our experience suggests that EPOCH with setting‐appropriate modifications may be a practical, safe, and effective option for improving high‐risk NHL outcomes in Malawi and comparable settings, which deserves further prospective evaluation.